South African Hacked Animation Methodologies: A Conceptual Foundation to Studying Animation Metamorphosis in Local Production Practices Post-2020 - Van Rooyen, Rachel (Proceedings of CAGA24: The Conference of AG Animation 2024, 2025)
South African animation studies have historically been constrained by outdated frameworks that fail to reflect current local production realities. This paper argues that contemporary South African animation must be analysed through locally adapted production methodologies, digital distribution strategies, and shifting intellectual property (IP) structures. The discourse around “authentic” African animation remains problematic, as outsourced productions are dismissed as “odourless,” while local content is critiqued for not being “native” enough. These views overlook how studios creatively adapt to economic, political, and infrastructural challenges through “hacked” production techniques—innovative, resourceful strategies that work around systemic limitations. With the rise of platforms like YouTube and Netflix, studios are bypassing traditional distribution barriers but still face algorithmic biases reinforcing dominant Western norms. This study calls for an updated and decolonised framework that addresses both Web 4.0 technologies and culturally situated analysis. Drawing on case studies of Rams Comics and Cabblow Studios, the paper highlights how animators assert creative agency and IP control.